Model Matematika Co-infection Tuberkulosis dan COVID-19 dengan Intervensi Obat Anti Tuberkulosis (OAT) - Safira Putri Islamiati; Eti Dwi Wiraningsih; Devi Eka Wardani Meganingtyas (JMT : Jurnal Matematika dan Terapan, 2023)
Tuberculosis and COVID-19 are deadly infectious diseases with similar symptoms which mostly attacks lung. When these infections conduct in a single host simultaneously, it will give a low chance of survival. This thesis constructed and analyzed a compartmental tuberculosis and COVID-19 co-infection with anti-tuberculosis drugs intervention model. Our model claimed that the equilibrium point of the co-infection model is stable when the basic reproduction number or the number of the secondary infections is below 1. Numeric simulation was given, using parameter value calculated from the data of tuberculosis and COVID-19 situation in Indonesia period of March 2020 until March 2021 along with the result displayed in graphic. The basic reproduction number were obtained accordingly with the parameter value by 0.1819422898. This means, there are no Tuberculosis and COVID-19 co-infection transmission inside the population.